2016
DOI: 10.1371/journal.pone.0166541
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life for Children and Adolescents with Specific Language Impairment: A Cohort Study by a Learning Disabilities Reference Center

Abstract: ObjectivesTo assess the health-related quality of life (HRQOL) of children with specific language impairment (SLI).Study DesignIn a prospective sample at a Learning Disabilities Reference Center, proxy-rated HRQOL (KIDSCREEN-27) was assessed for children with SLI and unaffected children from January 1, 2014 to March 31, 2015. Quality of life predictors for children with SLI were evaluated by recording the length and number of speech therapy and psychotherapy sessions and the specific school organization that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 39 publications
3
32
0
1
Order By: Relevance
“…Our results showed that in 25% of the studies, the authors gave reasons for choosing an instrument. For instance, pointed Hubert-Dibon et al [17] out that they chose the KIDSCREEN-27questionnaire because the instrument provides a broad perspective on understanding of HRQOL, it includes five dimensions and requires only 10–15 min to complete, but still permits evaluation of the main components of HRQOL [17]. However, few studies have distinguished QOL from HRQOL, only 6% of the articles found in our study did so.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our results showed that in 25% of the studies, the authors gave reasons for choosing an instrument. For instance, pointed Hubert-Dibon et al [17] out that they chose the KIDSCREEN-27questionnaire because the instrument provides a broad perspective on understanding of HRQOL, it includes five dimensions and requires only 10–15 min to complete, but still permits evaluation of the main components of HRQOL [17]. However, few studies have distinguished QOL from HRQOL, only 6% of the articles found in our study did so.…”
Section: Discussionmentioning
confidence: 79%
“…QOL research has been criticized for a lack of conceptual clarity and clear definition of QOL [8, 1517]. In this snapshot review, most articles had a low-quality score according to the criteria of Gill and Feinstein [5, 8].…”
Section: Discussionmentioning
confidence: 99%
“…Studies focused on QoL in children with communication impairments, ranging in age from birth to 18 years, consistently find negative impacts on social functioning, e.g., difficulties getting along with others (Feeney et al 2012), as well as difficulties in psychosocial well-being and school functioning (Hubert-Dibon et al 2016, McKean et al 2017. Interpersonal relations, participation in school and play activities, learning, socializing, and behaviour were all identified as areas of concern by parents and clinicians describing children's (2-5 years) well-being in open-ended survey questions before starting therapy (n = 210) (Thomas-Stonell et al 2009).…”
Section: Qol In Children With Dldmentioning
confidence: 99%
“…), as well as difficulties in psychosocial well‐being and school functioning (Hubert‐Dibon et al . , McKean et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, epidemiological approaches involving screening large numbers of children consistently show prevalence rates of 7–8% for developmental language disorder (DLD; Tomblin et al, 1997 ), but only parents of a quarter of these children were aware their child had a speech or language problem. These low identification rates are relevant because speech/language disorders cause life-long difficulties in academic, social, and economic domains ( Baker & Ireland, 2007 ; Beitchman, Nair, Clegg, & Patel, 1986 ; Cantwell & Baker, 1987 ; Catts, 1993 ; Conti-Ramsden, Durkin, Toseeb, Botting, & Pickles, 2018 ; Hall & Tomblin, 1978 ; Hubert-Dibon, Bru, Le Guen, Launay, & Roy, 2016 ; Law, Rush, Schoon, & Parsons, 2009 ; Paul & Cohen, 1984 ; Rice, Sell, & Hadley, 1991 ). Children with dyslexia and DLD are also far more likely to enter into the juvenile justice system ( Snow, 2019 ).…”
Section: Introductionmentioning
confidence: 99%